2019
DOI: 10.4028/www.scientific.net/msf.961.107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing Salinity to Corrosion Resistance of 5052 Aluminum Alloy in Artificial Seawater

Abstract: The purpose of this research is to investigate the corrosion resistance of 5052 aluminum alloy to increasing salinity in sea water. Salt spray chamber was used to measure and compare the corrosion rate of 5052 aluminum alloy with weight reduction method. The experiment was conducted by varying the three concentrations of NaCl solution to compare the corrosion rate of the metal. The test specimens used were aluminum alloy 5052 with length of 6 cm, width of 4 cm and thickness of 0.7 cm. The tests were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Their study demonstrated that escalating NaCl concentrations from 3.5 to 10% led to a decrease in corrosion rate. Likewise, in 2019, Darmawan, Agung Setyo, et al 22 investigated the influence of salinity on aluminum alloy in artificial seawater and reported a similar correlation. This behavior can be attributed to the reduction in oxygen solubility accompanying increased water salinity, subsequently lowering water conductivity and, consequently, diminishing the corrosion rate 23 , 24 .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Their study demonstrated that escalating NaCl concentrations from 3.5 to 10% led to a decrease in corrosion rate. Likewise, in 2019, Darmawan, Agung Setyo, et al 22 investigated the influence of salinity on aluminum alloy in artificial seawater and reported a similar correlation. This behavior can be attributed to the reduction in oxygen solubility accompanying increased water salinity, subsequently lowering water conductivity and, consequently, diminishing the corrosion rate 23 , 24 .…”
Section: Resultsmentioning
confidence: 74%
“…Likewise, in 2019, Darmawan et al . 22 investigated the influence of salinity on aluminium alloys in artificial seawater and reported a similar correlation. The reason for these finding could be a reduction in oxygen solubility accompanying increased water salinity, subsequently lowering water conductivity and, consequently, diminishing the corrosion rate 23 , 24 .…”
Section: Introductionmentioning
confidence: 73%
“…The corrosion rate of metal is a key parameter by which to express the corrosion resistance of the alloys and their joints [ 32 , 33 , 34 ]. In the case of uniform corrosion and proper removal of corrosion products from the metal surface, the corrosion rate is expressed as Equation (1).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, aluminum is a non-ferrous metal that is most widely used in many branches of industry because of its superior and superior properties, especially Aluminum-silicon (Al-Si) alloys. In its development, Aluminum-silicon is widely used as a material for making a product because it has excellent castability, good weldability, good thermal conductivity, high strength at high temperatures, and excellent corrosion resistance [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%